Antibacterial Activity of Fe3O4/Cu Nanocomposite: Green Synthesis Using Carum carvi L. Seeds Aqueous Extract. Issue 2 (11th January 2019) - Heydari, Rouhollah; Koudehi, Masoumeh Foroutan; Pourmortazavi, Seied Mahdi
Abstract: Here, we describe the using of biosynthesis method for the synthesis of Fe3 O4, Cu nanoparticles and Fe3 O4 /Cu nanocomposite using Carum carvi extract and assessment of their antibacterial activity. Our approach is eco‐friendly, non‐toxic and clean. These nanoparticles/nanocomposites were characterized by UV‐Vis, FTIR, XRD, EDX and SEM, techniques. The findings indicated that the of Fe3 O4 and Cu NPs, and Fe3 O4 /Cu nanocomposite have an average particle size of 25 nm, 37 nm, and 62 nm, respectively. On the other side, the Fe3 O4 NPs do not have the antibacterial activity, but when they combine with Cu NPs with antibacterial activity, the Fe3 O4 /Cu nanocomposite shows the antimicrobial activity. Abstract : Biosynthesis method is used for the synthesis of Fe3 O4, Cu nanoparticles and Fe3 O4 /Cu nanocomposite using Carum carvi extract and assessment of their antibacterial activity. The results showed that the composite is made of only Fe, Cu and O. After the Fe3 O4 /Cu NPs nanocomposite is prepared, the results showed that the nanocomposite also possesses the magnetic properties of Fe3O4 NPs, as well as the antibacterial properties of Cu NPs.